2011
DOI: 10.21101/cejph.a3621
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cigarette Smoking and its Relation to Certain Risk Predictors of Cardiovascular Diseases in Central-Slovakian Roma Children and Adolescents

Abstract: SUMMARYThe objective of the study was to determine some Cardiovascular Disease (CVD) risk factors in relation to cigarette smoking in 174 Roma children and adolescents (88 males and 86 females) and 131 non-Roma probands (males and females) aged 7-18 in central Slovakia.In this biethnic study, 26.4% of the Roma children and adolescents (more than twice contrary to the control group) were smokers. Among the studied ethnicities, the majority of smokers was Roma (79.3%, 46 subjects). Smoking Roma have higher means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…Our comparative study demonstrated that children living in Roma settlements have many unfavourable health behaviour indicators compared with the general youth population mainly at the age 11. Similar findings were reported in other reports (32)(33)(34). The self-rated health status of Roma children was worse than that of the children in the general population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our comparative study demonstrated that children living in Roma settlements have many unfavourable health behaviour indicators compared with the general youth population mainly at the age 11. Similar findings were reported in other reports (32)(33)(34). The self-rated health status of Roma children was worse than that of the children in the general population.…”
Section: Discussionsupporting
confidence: 91%
“…Roma families, particularly families living in settlements, are more strongly affected by poverty and social deprivation than the average population because of their low education level and high unemployment rate (31). Recently, an increasing number of papers have focused on health status and health behaviours of this socially and economically disadvantaged group (19,(32)(33)(34). These studies have mainly focused on isolating behavioural characteristics, while only a few studies carried out comprehensive surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking habit and high level of tolerant attitude towards smoking characterize the Roma people worldwide (Gerevich et al, 2010;Hujova et al, 2011;Paulik et al, 2011). The present study showed that the Roma population bears an enormous CVD risk due to a huge prevalence of smoking; over 70% persons are current smokers compared to 30% in the general Croatian population (Č ubrilo-Turek et al, 2003).…”
Section: Comparison Of Cvd Risk Factors Prevalence By Sexmentioning
confidence: 50%
“…Пассивное курение влияет на функцию эндотелия, стимулируя выработку цитокинов, провоспалительных интерлейкинов, фибриногена, стимулирует пролиферацию глад комышечных клеток, активацию XII фактора, поражает образование и функцию тромбоцитов, в том числе лейкоцитарную адгезию. Сига ретный дым содержит различные окислители (свободные радикалы кислорода и летучие аль дегиды), которые активно участвуют в форми ровании атеросклероза [12,18]. Согласно иссле дованиям Apfelbacher и соавт., у новорожден ных, подвергающихся воздействию сигаретного дыма в первые годы жизни, повышается риск развития избыточного веса или ожирения [3].…”
Section: результаты исследованияunclassified